Perlindungan Hukum Terhadap Pekerja dalam Hal Perusahaan Mengalami Kepailitan dan Penundaan Kewajiban Pembayaran Utang - Ni Putu Trisna Dewi; I Nyoman Putu Budiartha (Fakultas Hukum, Universitas Warmadewa, 2022)
Bankruptcy is the legal position accepted by the debtor because of the bankruptcy decision by the justice institution. As a result of the bankruptcy decision, the debtor's assets are placed under confiscation which can make the debtor unable to own his wealth. This is because until the bankruptcy estate is settled by the bankruptcy estate manager in Bankruptcy Legal and PKPU is called a Curator. This study describes the form of legal protection for workers in the event that the company experiences bankruptcy and delays debt payment obligations. This research uses normative regulatory research and legal and conceptual approaches. Sources of data in the study using primary, secondary, and tertiary legal materials. Qualitative methods are used to analyze the data in drawing conclusions. The end of this discussion explains the rights obtained by workers when their company goes into bankruptcy as regulated in the Manpower Regulations and legal remedies for workers to obtain their rights related to the company's obligations related to bankruptcy and postponement of obligations to pay debts by filing a PKPU so that debtors can submit a plan to make peace by offering an offer to pay debts to creditors.